Immigration policy and the skills of Irish immigrants: evidence and the implications - Minns, Chris (Statistical and Social Inquiry Society of Ireland, 2005)
The rise of immigration into Ireland has been accompanied by a debate on the potential objectives of immigration policy. This paper begins with a survey of international and historical evidence on the economics of immigration policy. To place Irish immigration in the international context, a recent OECD data set is used to compare the education of Irish immigrants to their counterparts in other European economies. The data suggest that Ireland's immigrant population is remarkably skilled. Immigrants of EU origin are positively selfselected. From outside the EU, some countries supply mainly skilled immigrants, while others are sources of less-skilled workers. These findings are used as a backdrop to explore three major issues in Irish immigration: the likely impact of EU accession of new member states, the appropriateness of current immigration policy, and the relationship between current immigration and future population flows.
read before the Society, 24 February 2005
Keywords: Ireland; immigration policy; immigration; immigrant skill; 314.15